Tuber iranicum, sp. nov., a truffle species belonging to the Excavatum clade. (2nd September 2020) - Puliga, Federico; Illice, Mirko; Iotti, Mirco; Baldo, David; Zambonelli, Alessandra
ABSTRACT: Truffles in the genus Tuber are hypogeus fungi that have a worldwide distribution. Despite this, knowledge about their diversity in the Middle East is very limited. In recent years, large quantities of truffles have been imported from Iran for being sold in Italy. While analyzing certain commercial batches of T. aestivum from Iran, we found some ascomata that resembled T. excavatum but had macro- and micromorphological features that were distinct from this species. They were subglobose, or depressed to slightly irregular, with a conspicuous basal cavity, grayish brown, brown, or pinkish gray, with a minutely papillose peridium. The gleba was pinkish gray in youth, brown at maturity, marbled with cream branched veins. Ascospores were broadly ellipsoid, with an irregular reticulum and distinctive long crests along the longitudinal axis, up to 9 µm high. Analysis of internal transcribed spacer (ITS) and large subunit (LSU) rDNA sequences showed that these specimens form a monphyletic and well-supported taxon within the Excavatum clade. Morphological and molecular analyses supported the proposal of the new species T. iranicum .